Analysis of Clean Ocean Campaign Framing in Instagram Account Posts @pandulaut.id and @theoceancleanup - Nur Rizky Ramadhania; Hidayat, Nurul (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2024)
The sea is one of the most vital habitats for all life on Earth. Known as a beautiful expanse of blue full of mystery, the ocean also harbors a significant unseen threat: pollution. The greatest current focus of marine threats lies in plastic waste, with an annual deposition of 8 million tons of plastic pollution into the oceans. This pollution has immense impacts on marine life, ecosystems, and human health. The clean ocean campaign movement represents a powerful effort to raise awareness and encourage communities to preserve marine cleanliness for the future of our planet. This study aims to analyze the framing of posts from two Instagram accounts advocating for ocean cleanliness: @pandulaut.id and @theoceancleanup. Using a qualitative method and Robert Entman's framing analysis model, the study focuses on four elements: problem definition, diagnosis of causes, moral considerations, and problem solutions. The findings from the study indicate that throughout 2023, both Instagram accounts highlighted posts defining marine pollution as a significant threat to marine life. They also featured educational and motivational content to inspire viewers. This research specifically examines how these two accounts disseminate their campaigns to raise public awareness and promote actions to maintain the cleanliness and sustainability of marine ecosystems.